Cultural Resilience of Adolescent Women in Pesantren - Widiyanti, Wiwied (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
This study aims to describe the cultural resilience of adolescent girl in Pesantren (Islamic boarding schools). The scope of this study includes: 1) General overview of culture resilience; and 2) implications on guidance and counseling. The method used in this study is descriptive quantitative with the following steps determine the respondents research, determine the model of the instrument, and distribute the instrument to the respondent. This research is expected to produce a concept of culture based resilience counseling as the basis for thinking in further research.